Neuroarchitectural principles applied to a geriatric center in District 12 of San Juan de Lurigancho (Lima, Peru) - Pillaca Alarcón, Alexandra Ana (2025)
The lack of adequate spaces for geriatric care and deficiencies in services aimed at improving the health and well-being of older adults are some of the problems facing this population; this has motivated us to investigate the impact of neuroarchitecture on the quality of life of older adults. This study aligns with SDG 3: Good Health and Well-being, and aims to investigate the neuroarchitectural principles that can be applied in the design of a geriatric center to improve the quality of life of older adults. In this regard, the study seeks to integrate landscaping, comfort, sensory stimulation, social interaction, and efficient architecture, and to address aspects of zoning, form, and aesthetics. It also identifies the essential services of a geriatric center. As a result, three important aspects for the design of a geriatric center stand out: emotional well-being, physical health, and the quality of life of older adults. Finally, it is concluded that the lack of geriatric centers in Commune 12 highlights the urgent need to develop an adequate infrastructure that integrates the principles of neuroarchitecture for the comfort and well-being of geriatric patients.